Venedig - Luigi Nono und die komponierte Stadt: Zur musikalischen Präsenz und diskursiven Funktion der Serenissima - Geiger, Friedrich 1966-; Janke, Andreas 1979- (Munster New York Waxmann, 2015)
The composer Luigi Nono was born in Venice in 1924. Apart from brief interruptions, he lived there until his death in 1990, repeatedly emphasising that the city was reflected in his music. This view has been taken for granted in the literature on Nono, but it is still unclear which of Venice's sonic reflections can be named in detail and what Nono's aims were. The authors of this volume pursue such questions systematically and critically by differentiating the references to Venice in Nono's music using the example of selected compositions. In addition, the composer's comments on his home city over a period of almost forty years are documented. The volume, edited by Friedrich Geiger and Andreas Janke, also contains previously unpublished reproductions of sketches by the composer, which are now kept in the Archivio Luigi Nono (Venice).
With contributions by David Albus, Noemi H. Deitz, Arne Gadomski, Friedrich Geiger, André-Philipp Hechinger, Andreas Janke, Tobias Knickmann, Inken Meents, Luigi Nono, Marvin J. Rehr, Lana Zickgraf
Bibliography pages [228]-235
Keywords: Nono, Luigi -- 1924-1990; Composing; Venice (Italy)